Website Quality and Corporate Financial Performance - Paul Watkins; Malcolm Smith (Journal of Accounting, Business and Management (JABM), 2008)
This paper explores the relationship between the quality of a companys website and aspects of corporate financial performance, for UK manufacturing companies. Survey and archival methods are used to measure website quality and financial performance, and to specify the relationship between the two. A significant relationship between financial gearing and website quality is observed, consistent with the findings from hardcopy corporate narratives. These findings are limited to listed UK manufacturing companies and may not be generalisable to smaller companies, other industries or different countries. The direction of causation has not been specified, but remains consistent with prior literature, in that excellent website quality may be signalling good financial performance. The findings have implications for the constructors of websites, in that they should be aware that the content and presentation of these sites will signal users with messages regarding the financial performance of the enterprise. In this regard the paper is the first to apply a specialised commercial survey instrument in the examination of the relationship between website quality and corporate performance.